Female soccer: Part 1 - A needs analysis. - Turner, E.; Munro, A.; Comfort, P. (Strength and Conditioning Journal, 2013)
It is imperative for strength and conditioning coaches to conduct a detailed analysis of the demands of a sport, identifying normative data where possible to permit an evidence-based evaluation of an athlete's current performance status and to inform the development of specific goals for the athletes' development. Part one of this article reviews the demands of female soccer and provides normative data from published research identifying specific areas that require development in female soccer players. Part two recommends evidence-based approaches integrated to athlete development and injury prevention strategies, as a result of the needs analysis.